Application of smartphone-based biophotonic instrumentation for glucose sensing using photometric method - Aziz, Nur Anis Huda (Universiti Sains Malaysia, 2024)
Glucose sensing is vital in health such as monitoring blood glucose levels in managing diabetes and food quality, for instance, adulterated honey detection. Current methods involve invasive, expensive equipment and highly trained personnel to carry out the test, which can limit the detection and application of glucose at on-site determination. This study aimed to apply smartphone-based biophotonic instrumentation for measuring glucose concentrations using the photometric method. The photonic device constructed consists of a 940 nm near-infrared light-emitting diode (NIR LED) as an emitter, a BPW34 photodiode as a detector, a Raspberry Pi Pico microcontroller board acts as a digital interface to convert the receiving data into output voltage, and an Android app; Scoppy as a digital oscilloscope to display the output voltage value on a smartphone. The instrument detected the glucose at different concentrations. A lower and higher range of glucose concentrations was tested which is 50 – 300 mg/dL for glucose in human body detection purposes, whereas 10 – 100 g/dL demonstrates the level of glucose in adulterated food such as honey. The findings indicated that higher glucose concentrations resulted in higher detector output voltages. The linear regression analysis obtained is R2 = 0.9389 with slope value of 0.0002 for lower and R2 = 0.9641 with slope value of 0.0011 for higher range of glucose concentration. Results obtained for photoabsorption and phototransmittance were A < 0, and T > 1, respectively, for both range of glucose concentrations. This study demonstrates a promising result in terms of feasibility, sensitivity, and applicability in integrating biophotonic instrumentation with a smartphone.